Workshop Pengembangan Produk dan Konten Marketing sebagai Strategi Pemasaran Digital Produk UMKM Desa Kemetul - Pujiastuti, Anasthasia; Setya Indah Isnawati; Jaya Ramadaey Bangsa; Gagah Dwi Wicaksono; Faturahman Efendi (UNIVERSITAS NGUDI WALUYO, 2024)
Kemetul Village is located in Susukan District, Semarang Regency, with the livelihoods of its people as farmers/planters and entrepreneurs. In Kemetul Village, there are many UMKM that utilize the harvest from plants. The understanding of business actors about developing new products from harvests and product marketing strategies that are still lacking, prompted the implementation team to carry out community service in Kemetul Village. Community service activities were carried out from July to September 2024. The methods used included surveys and interviews with village officials and the head of the